High-Speed Synchronous Reluctance Machine Rotor Using Multi-Material Additive Manufacturing - Klima, Petr; Barta, Jan; Koutny, Daniel; Vitek, Ondrej (IEEE transactions on energy conversion, 2025)
High-speed machines are popular in industry due to their high power density. Permanent synchronous machines are commonly preferred, but they rely on rare earth magnets, which are expensive and environmentally demanding. Axially laminated anisotropic synchronous reluctance machines, a promising alternative, are currently limited to two poles and simple rotor geometry. This paper proposes a modified axially laminated anisotropic geometry, produced using multi-material additive manufacturing, to overcome these limitations in a high-speed synchronous reluctance machine. Magnetic 17-4PH and non-magnetic 316L steels were selected as suitable materials for a case study machine. To determine the effect of heat treatment on the magnetic properties of an additively manufactured 17-4PH steel sample, magnetic measurements were conducted. A 60 000-rpm case study machine was optimized using a non-dominated sorting genetic Algorithm 2, resulting in a machine with a shorter active length. Tests conducted during and after manufacturing verified the feasibility of the proposed rotor solution. This development expands the potential use of axially laminated anisotropic topology and synchronous reluctance machines in high-speed applications. Additionally, the successful use of multi-material additive manufacturing technology in the field of electrical machines is demonstrated.